Optimizing the Performance of the Sragen Police Traffic Unit Gakkum in Implementing Restorative Justice for Traffic Accident Law Enforcement - Azis Alfare (Tanggon Kosala, 2022)
The problem of traffic accidents, especially at the Sragen Police, continuesto increase from year to year. The number of traffic accidents at the SragenPolice Station is quite high in Central Java Province. In law enforcementSragen Police often use Restorative Justice. There is a need to optimize theperformance of the Satlantas Police Unit of the Sragen Police inimplementing Restorative Justice so that it can provide benefits to reducetraffic accidents at the Sragen Police. The issues to be discussed areregarding the performance of the Sragen Police Satlantas Unit and theorganizational resources of the Sragen Police Satlantas Unit inimplementing Restorative Justice. In order to be able to answer thisproblem, a research was carried out in the Sragen Police area usingmanagement theory, Organizational Resources, and SWOT. There areseveral findings in the research that has been conducted that theperformance of the Sragen Police Satlantas Unit in implementingRestorative Justice is still not optimal and the organizational resources ofthe Sragen Police Satlantas Unit in implementing Restorative Justice arestill not optimal. In order to be able to provide solutions to existing problems,solutions to problems can be provided such as the need for optimization ofplanning, implementation and supervision by the Gakkum Unit and the needfor optimization of the utilization of personnel, budgets, methods andfacilities